Impact of nurse practitioners in community-based interventions for physical and mental health - Sarin, Jyoti; Singh Charan, Gopal; Kaur, Ekjot; Phougat, Jyoti (Journal of Chitwan Medical College, 2025)
Nurse practitioners, usually a registered nurse with advanced clinical training, have an influential role in health care system. By stimulating the general public regarding lifestyle modifications, they can be productive in the vast sphere of public health, contributing significantly to the reduction of health risks in families and communities. Nurse practitioners conduct systematic screenings to detect several infectious diseases in the initial stages and implement client-focused interventions, which can have a positive financial impact on the disease burden and ultimately improve community health outcomes. Moreover, they raise public awareness about non-communicable diseases such as cardiac disorders, cancer and diabetes mellitus, which remain the leading causes of death in the current framework of health conditions. Nurse practitioners recognize mental illness by screening through mental status examinations for conditions like depression and anxiety. They can collaborate with physicians, psychiatrists, psychologists, therapists and other health professionals to provide integrated care. Despite the possibility of their profuse contributions in the field of public health, nurse practitioners still face challenges in impersonating their role in public health for several reasons. They have limited authority in treatment and management when compared to physicians. There is no global policy or uniformity of rules regarding training and competence-based education; different countries have different policies. These barriers hamper their full integration into public health care. In conclusion, health organizations should develop global policies to empower nurse practitioners to provide comprehensive patient care.